Threat of a Measles outbreak amidst COVID 19 surge in Sindh, Pakistan- Letter to the editor - Zainab Ahmad; Hira Zahid (Journal of the Pakistan Medical Association, 2021)
The manuscript comments on the rise of suspected measles cases amidst the COVID 19 pandemic in Sindh, Pakistan. It emphasizes the shortcomings and urges prompt action to prevent an epidemic in the region as an immediate consequence of COVID 19. A potential measles outbreak would result in a major setback to our health care system. Continuous...